Idiopathic Granulomatous Mastitis with Skin Rupture: A Retrospective Cohort Study of 200 Patients Who Underwent Surgical and Nonsurgical Treatment. Issue 7 (9th August 2021) - Wang, Jiangfen; Zhang, Yafen; Lu, Xiaoting; Xi, Chunfang; Yu, Keda; Gao, Runfang; Bi, Kaixin
Abstract: Background: Idiopathic granulomatous mastitis (IGM) can clinically and radiographically mimic an abscess or breast cancer. Although IGM is benign, it can cause the breast skin to appear "riddled with holes" and can even result in the loss of the breast. The optimal treatment has not been established. Methods: We retrospectively studied the medical records of 200 patients with IGM who were treated for skin rupture from June 2015 to June 2017 in our institute. The patients' treatment modalities (including surgery after steroid therapy and steroid therapy alone), outcomes, and scores of satisfaction questionnaires were analyzed. The time to healing and recurrence rate were compared with a focus on the treatment modalities to identify the most effective treatments for IGM. Results: The median follow-up time was 15.64 months (range, 12–36 months). In total, 156 patients were treated with surgery after steroid therapy and 44 were treated with steroid therapy alone. The median times to healing in the surgical and nonsurgical groups were 25 and 258 days, respectively ( p = 0.003). Four of 156 (2.56%) patients developed post-excision wound complications. Eight of 156 patients (5.1%) in the surgical group and 10 of 44 (22.7%) patients in the nonsurgical group developed recurrence ( p < 0.01). The scores of the satisfaction questionnaire were 36 ± 4.28 in the surgical group and 24 ± 8.62 in the nonsurgical group ( p = 0.017). Conclusion: IGM is a benign disease but can have serious consequences. Surgery after steroid therapy is an effective and more satisfactory treatment than steroid therapy alone.